Mengelola Konflik Dalam Komunikasi Online: Etika dan Keamanan di Dunia Digital - Matondang, Ahmad Sultoni (Jurnal Dakwah dan Masyarakat, 2025)
This research aims to analyze the forms of conflict that arise in online communication and examine the role of digital ethics and security as strategies for creating a healthy and safe digital communication space. The method used is qualitative through content analysis and in-depth interviews with five informants selected using purposive sampling, including active social media users, digital community moderators and communications experts. Data was collected from various digital platforms indicating conflicts, ethical violations and security threats, then analyzed using thematic analysis techniques. The research results show that conflict in online communication is triggered by the loss of non-verbal cues, anonymity, differences in values, gaps in response time, and low digital literacy. Digital ethics, such as honesty, respect, responsibility and preservation of privacy, have proven to play an important role in mitigating conflict, while digital security contributes to protecting users from cyber risks. This research implies the need to strengthen digital literacy, community guidelines, and moderation policies to build a more ethical, safe, inclusive, and constructive communication environment in the digital era. Penelitian ini bertujuan untuk menganalisis bentuk-bentuk konflik yang muncul dalam komunikasi online serta mengkaji peran etika digital dan keamanan sebagai strategi untuk menciptakan ruang komunikasi digital yang sehat dan aman. Metode yang digunakan adalah kualitatif melalui analisis konten dan wawancara mendalam terhadap lima informan yang dipilih secara purposive sampling, meliputi pengguna aktif media sosial, moderator komunitas digital, dan ahli komunikasi. Data dikumpulkan dari berbagai platform digital yang menunjukkan adanya konflik, pelanggaran etika, dan ancaman keamanan, kemudian dianalisis menggunakan teknik analisis tematik. Hasil penelitian menunjukkan bahwa konflik dalam komunikasi online dipicu oleh hilangnya isyarat non-verbal, anonimitas, perbedaan nilai, kesenjangan waktu respons, serta rendahnya literasi digital. Etika digital, seperti kejujuran, rasa hormat, tanggung jawab, dan pemeliharaan privasi, terbukti berperan penting dalam meredam konflik, sedangkan keamanan digital berkontribusi pada perlindungan pengguna dari risiko siber. Penelitian ini mengimplikasikan perlunya penguatan literasi digital, pedoman komunitas, dan kebijakan moderasi untuk membangun lingkungan komunikasi yang lebih etis, aman, inklusif, dan konstruktif di era digital.